Attractiveness of Golden Hamster infected with Leishmania amazonensis (Kinetoplastida: Trypanosomatidae) to laboratory-reared Lutzomyia longipalpis (Diptera: Psychodidae) - da Rocha Silva, Flávia Benini [UNESP]; Miguel, Danilo Ciccone; Minori, Karen; Grazzia, Nathália; Machado, Vicente Estevam [UNESP]; de Oliveira, Cíntia Marcelo [UNESP]; Tosta, Christiann Davis; Pinto, Mara Cristina [UNESP] (Elsevier, 2024)
Lutzomyia longipalpis is the primary vector of Leishmania infantum in the Americas and a permissive vector for Leishmania amazonensis. Previous studies showed that Leishmania infantum-infected hosts can release different volatile organic compounds (VOCs) compared with uninfected hosts, presenting a higher attractiveness to vectors. In this study, we aimed to evaluate a possible effect of L. amazonensis infection of golden hamsters in three parameters: attractiveness to Lu. longipalpis females; blood volume ingested by sand fly females; and VOCs released by the animals. Attractiveness was measured indirectly by the number of Lu. longipalpis females that blood fed in each L. amazonensis-infected and uninfected animal. For VOCs extraction, solid phase micro extraction fibers were used, which were analyzed by gas chromatography-mass spectrometry. Behavioral trials did not show any effect of L. amazonensis infection on the attraction of sand flies nor difference on blood meal rates of Lu. longipalpis fed in both goups of hamsters. Additionally, there was no difference between the VOCs profiles of L. amazonensis-infected or uninfected hamsters.
Keywords: Cutaneous leishmaniasis; Kairomones; Sand flies; Volatile organic compounds